Driving Demand Transforming B2B Marketing to Meet the Needs of the Modern Buyer - Hidalgo, Carlos; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Carlos Hidalgo provides a clear roadmap and framework on how B2B organizations can implement change management and transform their Demand Generation. Case studies and excerpts from B2B marketing practitioners and ANNUITAS clients who have transformed their organizations and how they accomplished this change are incorporated throughout the book.
Keywords: Business; Marketing; Market research; Management; Organization; Planning; Sales management; Economics; Management science; Business and Management; Management; Marketing; Organization; Market Research/Competitive Intelligence; Sales/Distribution.; Economics, general; Electronic books